2017
DOI: 10.1159/000475768
|View full text |Cite
|
Sign up to set email alerts
|

Consensus on Stereotactic Body Radiation Therapy for Small-Sized Hepatocellular Carcinoma at the 7th Asia-Pacific Primary Liver Cancer Expert Meeting

Abstract: Background: Stereotactic body radiation therapy (SBRT) is an advanced technique of external beam radiation therapy that delivers large ablative doses of radiation. In the past decade, many cancer centers have adopted SBRT as one mode of radically treating small-sized hepatocellular carcinoma (HCC), based on encouraging clinical outcomes. SBRT thus seems reasonable as first-line treatment of inoperable HCC confined to the liver. However, most of the clinical studies to date have been retrospective in nature, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 58 publications
0
43
0
Order By: Relevance
“…This study confirms the wide variation of regimens used in clinical practice and identifies 50 Gy in five fractions as the most common scheme in this cohort of patients treated in the United States, which is also the recommended dose on the currently enrolling RTOG 1112 protocol, if liver constraints can be achieved. The variation in treatment regimens reflects the multiple factors that are considered in determining the dose including the size and location of the lesion, the radiation tolerance of nearby organs, liver health, the amount of liver spared from significant radiation doses, institutional preference, and organ motion managment …”
Section: Discussionmentioning
confidence: 99%
“…This study confirms the wide variation of regimens used in clinical practice and identifies 50 Gy in five fractions as the most common scheme in this cohort of patients treated in the United States, which is also the recommended dose on the currently enrolling RTOG 1112 protocol, if liver constraints can be achieved. The variation in treatment regimens reflects the multiple factors that are considered in determining the dose including the size and location of the lesion, the radiation tolerance of nearby organs, liver health, the amount of liver spared from significant radiation doses, institutional preference, and organ motion managment …”
Section: Discussionmentioning
confidence: 99%
“…Previous prospective and retrospective studies have shown excellent results of SBRT on small and early stage HCC, [ 14 ] however, until now there was limited data of the use of SBRT on BCLC stage C HCC. As BCLC-C is a heterogenous population with various adverse features and a dismal prognosis, delivering high doses to this group of patients is often challenging as higher mean radiation doses to the liver might compromise the liver function and increase the risk for liver failure.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have suggested avoiding SBRT in patients with Child-Pugh score of B8 and above except as a bridge to transplant [63,64], other studies of SBRT have included small numbers of such patients with encouraging results [65,66]. A recent consensus statement recommends that SBRT be used with caution in all ChildPugh B patients and only at low-dose volumes [67]. Clinical practice in Hong Kong is to treat selected Child-Pugh B8 patients with SBRT at the discretion of the treating physicians.…”
Section: Role Of External Radiotherapymentioning
confidence: 99%